Generalized Complementarity Problem with Three Classes of Generalized Variational Inequalities Involving ⊕ Operation - Rais Ahmad; Iqbal Ahmad; Zahoor Ahmad Rather; Yuanheng Wang (Journal of Mathematics)
In this study, we introduce and study a generalized complementarity problem involving XOR operation and three classes of generalized variational inequalities involving XOR operation. Under certain appropriate conditions, we establish equivalence between them. An iterative algorithm is defined for solving one of the three generalized variational inequalities involving XOR operation. Finally, an existence and convergence result is proved, supported by an example.